PROSPECT OF MINERAL AND COAL MINING POLICY - Pertiwi, Rahni Andeka; Manik, Berliandy Haposan; Praditha, Azzahra Ayu; Safitri, Nur (Pusat Unggulan Ipteks-PUI Universitas Jambi, 2023)
Mineral and coal mining policy is a subject that continues to receive attention in the legal and regulatory environment. This journal analyzes prospective mineral and coal mining policies through a normative juridical approach focusing on relevant regulatory aspects and legal implications. This study uses a normative juridical analysis method to evaluate policies that apply in the context of mineral and coal mining. This research gains an in-depth understanding of the existing regulatory structure by reviewing applicable laws and regulations, court decisions, and decisions of regulatory agencies. The results of this study indicate that mineral and coal mining policies have a solid legal basis and regulate various aspects, such as licensing, environment, labor protection, and corporate social obligations. However, there are challenges related to law enforcement, harmonization of regulations, and consistent implementation of policies. In response to these challenges, this study proposes several recommendations to increase the effectiveness of mineral and coal mining policies legally. These recommendations include expanding cooperation between relevant government agencies, improving regulations and procedures, increasing legal capacity, and strengthening oversight and stricter law enforcement. This research is expected to contribute to policymakers, legal practitioners, and related parties in developing more responsive, comprehensive, and effective regulations in maintaining the sustainability of the mineral and coal mining sector by taking into account related legal aspects.